2002
DOI: 10.1021/jf010776z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Isotopic Profile in the Characterization of Sugars. Influence of the Metabolic Pathway

Abstract: The site-specific natural hydrogen isotope ratios of plant metabolites determined by 2H nuclear magnetic resonance (SNIF-NMR method) can provide powerful criteria for inferring mechanistic and environmental effects on biosynthetic pathways. This work examines the potential of isotopic profiles for the main constituents of carbohydrates, glucose and fructose, to distinguish different photosynthetic pathways. An appropriate analytical strategy, involving three suitable isotopic probes, has been elaborated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 20 publications
4
45
0
2
Order By: Relevance
“…Although photorespiration leads to C loss, 3-phosphoglycerate (3-PGA) is formed after both carboxylation and oxygenation, but with differing stoichiometries and along differing paths. Numerous observations have shown that synthesis of a compound via different pathways induces different isotopomer distributions (18,19,(28)(29)(30)(31)(32). No exception to this rule has been observed, and it agrees with the theory of isotope effects.…”
Section: /D6supporting
confidence: 81%
“…Although photorespiration leads to C loss, 3-phosphoglycerate (3-PGA) is formed after both carboxylation and oxygenation, but with differing stoichiometries and along differing paths. Numerous observations have shown that synthesis of a compound via different pathways induces different isotopomer distributions (18,19,(28)(29)(30)(31)(32). No exception to this rule has been observed, and it agrees with the theory of isotope effects.…”
Section: /D6supporting
confidence: 81%
“…Glucose slightly bideuterated at 6R,6S (6,6 designates the average of these positions) was used to test that no ethanol was produced by glycolysis. Glucose from corn (Zea mays) was used as reference, the natural abundance ( 2 H/ 1 H) j having been previously determined for each hydrogen position j (19). Fermentation was also performed with slightly deuterated water to determine the extent to which this was a source of hydrogen in ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 3). Glucose from corn (Zea mays) was used as reference, and the natural abundance (D/H) i was determined for each hydrogen position (16) Thus, the affiliation was measured at natural abundance and at a 3-5-fold site-specific enrichment. In all fermentations conducted with either Lc.…”
Section: Resultsmentioning
confidence: 99%